Exploring students' perceptions of multicultural religious education: Strategies for promoting multicultural values in social and educational environments - Rahmania, Sheila Anisa (Asian Journal Collaboration of Social Environmental and Education, 2025)
Background: Multicultural education has emerged globally as a response to the undeniable reality of multiculturalism, driven by the struggle for human rights, democracy, and equality. The diversity of ethnicities and cultures in Indonesia forms the background of this research. Diversity contributes to national development; however, issues in Indonesia also demonstrate how diversity can lead to violence and loss. Methods: This study aims to explore students' perceptions of multicultural religious education and their views on the strategies used to instill multicultural values. To ensure scientific rigor, methods such as observation, interviews, and documentation were employed, supported by relevant references. Findings: Public Vocational Secondary Schools/Sekolah Menengah Kejuruan Negeri 1 Purwokerto (SMKN 1 Purwokerto) provides dedicated spaces for each religion practiced within the school. Additionally, the school organizes a monthly "Religious Friday" event to strengthen the spiritual well-being of both students and teachers. During these events, the school invites religious leaders to deliver lectures. Despite not all students being Muslim, the school strives to be fair; Christian students, for instance, are encouraged to attend church for worship and participate in the "Religious Friday" program. Conclusion: Similarly, even if there is only one student practicing Hinduism, Confucianism, or another religion, the school ensures that a religious leader is invited to address their needs SMK Negeri 1 Purwokerto is firmly committed to implementing a multicultural-based educational curriculum. Novelty/Originality of this article: This research provides new insights into schools’ commitment to inclusivity and the promotion of spiritual well-being through diverse religious practices.